STRATEGI PROMOSI “LANGKAH HALAL WEDDING ORGANIZER” DALAM MENCAPAI TARGET PASAR: STUDI PERSONALITAS DAN MOTIVASI YANG MENDASARI KONSUMEN DALAM MEMPERCAYAI “LANGKAH HALAL WEDDING ORGANIZER” - Nona Ratna Wulaksi, Achiriah, Abdul Rasyid (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Abstract: The study is a qualitative type of descriptive study, the data in the study is derived from primary and secondary data. The data-collecting technique used consists of interviews, direct observations, and documenting the results of this study explaining that either way or promotional strategies are done by the "Langkah Halal WeddingOrganizer" in reaching market goals, so that the public knows the whereabouts of the wedding organizer themselves. In this study has also produced several strategies to manage a wedding organizer through motivating or changing mindset audiences, that matrimony is the most important moment in life and once in a lifetime. By changing mindset like that, the society does the roots make the wedding a mediocre moment. To capture a bestmoment in memory must require a truly thoughtful service to organize the event to the best of all possible wedding organizers.